The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1063/5.0069884
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and estimation of Curie temperature in Ca2BIrO6 (B = Cr, Fe) double perovskites

Abstract: We investigate the electronic and magnetic properties of Ca2CrIrO6 and Ca2FeIrO6 by means of density functional theory. These materials belong to a family of recently synthesized Ca2CrOsO6 whose properties show possible applications in a room temperature regime. Upon replacement of Os by Ir in Ca2CrOsO6, we found the system to exhibit a stable ferrimagnetic configuration with a bandgap of ∼0.25 eV and an effective magnetic moment of ∼2.58μB per unit cell. Furthermore, when chemical doping is considered by repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
3
7
0
Order By: Relevance
“…The results of the relaxation for lattice constants and volume for both compounds are summarized in Table 1, where we see that the ferrimagnetic (FIM) ground state is the most stable since the corresponding energy is minimal. The results also revealed that the two compounds exhibit a monoclinic structure (space group P21/c) figure 1; our theoretical results agree with those reported in reference [16,20].…”
Section: Structural Propertiessupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the relaxation for lattice constants and volume for both compounds are summarized in Table 1, where we see that the ferrimagnetic (FIM) ground state is the most stable since the corresponding energy is minimal. The results also revealed that the two compounds exhibit a monoclinic structure (space group P21/c) figure 1; our theoretical results agree with those reported in reference [16,20].…”
Section: Structural Propertiessupporting
confidence: 91%
“…To explore the effect of spin-orbit coupling and on-site Coulomb repulsion (DFT+SO) and (DFT+SO+U) were introduced. The added Hubbard potential U was used with U=1.5 eV for Ir and U=4 eV for Co [20] and U=5 eV for Fe [16]. The convergence criterion for the self-consistent calculation was 0.0001 Ry for the total energies.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…GaAs, as an example, has the following benefit over Si: (i) A six times increase in electron mobility that enables quicker functioning; (ii) A wider band gap, which enables power devices to operate more faster at higher temperatures and produces less thermal noise at ambient temperatures; (iii) Its optoelectronic properties are more advantageous than those of indirect band gap Si because it has a direct band gap; (iv) For alloying, ternary and quaternary compositions are recommended. In compound semiconductors, nonmagnetic (NM), ferromagnetic (FM), antiferromag-netic (AFM) and ferrimagnetic (FIM) semiconductor are extensively studied theoretically as well as experimentally [3][4][5][6]. As a NM semiconductor transistor, bulk inversion asymmetry in (110) InAs/GaSb/AlSb heterostructures was proposed [7].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, layered perovskites Sr4Co3O10 and Sr4Rh3O10 shows HM-FM state [22] while FiM to HM-FiM and HM-AFM were observed in Pr2-xSrxMgIrO6 (x = 0 to 2) [23]. Many DPs are reported to have high Curie temperature (TC) [24][25][26]. One such example is Sr2CrOsO6 whose Tc is found to be 725 K [27].…”
Section: Introductionmentioning
confidence: 99%